An Efficient Synthesis of Imidazo[1,2-a]pyridines - Paengphua, Piyawat; Wichai, Uthai; Chancharunee, Sirirat (Naresuan University Journal: Science and Technology (NUJST), 2019)
Imidazo[1,2- a ]pyridines are useful building blocks for a number of biologically and pharmaceutically valuable compounds. Its synthetic method started from the reaction of 2-aminopyridines with acetophenones. However, the existing synthetic methods have drawbacks such as relatively high reaction temperatures, long reaction times and the difficult post-treatment. In this article, an improved synthetic method with high yield and simple steps for the synthesis of imidazo[1,2- a ]pyridines was reported. It is an improved method that CsF-Celite was used in post-treatment, which enhanced the total yield, and the operations were effectually simplified by the one-pot method. Moreover, CsF-Celite can be recovered for subsequent reactions and reused without any loss of efficiency. Keywords: Celite, Cesium Fluoride, One-pot synthesis